Simple fluid in an attractive, disordered polydisperse matrix - Patsahan, T.; Holovko, M. (Condensed Matter Physics, 2004)
The extension of the replica Ornstein-Zernike (ROZ) equations is applied to the study of the structural properties of a Lennard-Jones fluid confined in an attractive polydisperse disordered matrix. The ROZ equations in combination with the orthogonal polynomial expansions for the correlation functions are used. The radial distribution functions are calculated for the adsorbed fluid at different temperatures. The effect of matrix polydispersity on the excess internal energy is considered in our study as well.